PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN TRANS METRO PEKANBARU - Harpadeles, Ian; ', Jushermi; Nursanti, Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to measure the impact of service quality and customer value on customer satisfaction and loyalty Trans Metro Pekanbaru. The population in this study is the Trans Metro Pekanbaru customers with a total sample of 100 respondents, using purposive sampling technique. Analysis of data using path analysis with SPSS version 17.0. The results showed that the variables of service quality significantly influence customer satisfaction. Customer value significantly influence customer satisfaction. Service quality significantly influence customer loyalty. Customer value not significant effect on customer loyalty. Effect on the Service Quality Customer Loyalty with Customer Satisfaction as a moderating variable. Customer Value influence on Customer Loyalty with Customer Satisfaction as a moderating variable on the Customer Trans Metro Pekanbaru.Keywords: Service Quality, Customer Value, Customer Satisfaction, Customer Loyalty.